Audit committee characteristics and sustainability performance in Nigerian listed banks - Alex Adegboye; Stephen Ojeka; Oluwaseyi Alabi; Udochukwu Alo; Adenike Aina (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This study investigates the influence of audit committee characteristics on the sustainability disclosure among the Nigerian listed banks. Using the Fixed Effect regression estimator of panel data for ten (10) listed banks in Nigeria over the period of 2014-2016, the result shows that the influence of audit committee independence and gender diversity of audit committee are significantly positive on the sustainability disclosure. However, the audit committee magnitude has a negative and significant influence on the sustainability disclosure. This paper is unique as we consider the importance of the gender diversity of the committee given its relative contribution to sustainability reporting quality. This study tends to provide insights on sustainability reporting and assist stakeholders in emphasizing on the importance of sustainability disclosure through the audit committee oversight.
Keywords: G32; G34; M14; M42; 650; audit committee characteristics; gender diversity; and sustainability reporting